Guided Bone Regeneration of an Atrophic Maxilla Using Heterologous Cortical Lamina - Carlos Polis-Yanes; Carla Cadenas-Sebastián; Patricia Gual-Vaqués; Raúl Ayuso-Montero; Antoni Marí-Roig; José López-López (Case Reports in Dentistry)
Alloplastic dental implants are currently the best way to replace lost teeth. In order to achieve good function and prognosis of dental implants, having bone and soft tissue to support them is necessary. When the amount of bone left is not enough to ensure the outcome of the implant, techniques such as shorts implants, zygomatic implants, or guided bone regeneration have been used. Even though autologous bone is mostly the “gold standard,” other biomaterials such as xenografts have led to the reduction of the morbidity of treatments and to the improvement of the regeneration technique outcomes. We present a clinical case of severe atrophy of the maxilla in which we used different types of biomaterials: heterologous cortical lamina, xenograft and autologous bone, and microscrews.